The role of health shocks after age 70 on housing and wealth profiles - Asiye Aydilek (PLoS ONE, 2025)
We conduct a novel investigation into the effects of uncertain health shocks and medical costs on the life cycle consumption, housing, and saving decisions. Our model aids in understanding the role of health shocks and medical costs after age 70 in explaining the lack of wealth and housing decumulation during retirement. We utilize a comprehensive life-cycle model that includes housing, as well as shocks to house price, labor income, and health. Our model could be useful for policy evaluation and future studies concerning older adults. Our first contribution to the previous literature is modeling the whole adult life-cycle. This enables us to determine whether decisions in youth and middle age are influenced by anticipated health shocks in old age. Our second contribution is modeling housing explicitly with health shocks. Conclusions regarding the savings puzzle may be significantly influenced by the explicit modeling of housing. We develop a more realistic model by relaxing some of the assumptions made in previous studies. We find that health shocks motivate the household to accumulate higher wealth before retirement. Moreover, as health shocks become more severe, individuals reduce their consumption and decumulate less wealth in old age. Health shocks help explain the flat trends observed in the housing and wealth profiles of older adults. The possible health shocks after age 70 affect the decisions in young and middle ages only marginally. The wealth profile in middle and old age is affected by health shocks.